2003
DOI: 10.1038/sj.bjc.6601141
|View full text |Cite
|
Sign up to set email alerts
|

Possible alternative carcinogenesis pathway featuring microsatellite instability in colorectal cancer stroma

Abstract: Differential microsatellite instability (MSI) in tumour epithelial and stromal compartments has not been well examined for colorectal cancers. Using laser-captured microdissection, separate specimens of these compartments of 40 sporadic colorectal cancers were sampled and MSI was tested with four markers. To examine the relation between the MSI phenotype in the stroma and other genetic events and histopathological features, p53 and K-ras gene mutations were analysed, and the expression of p53, hMLH1, and hMSH2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 17 publications
1
39
1
Order By: Relevance
“…Various studies have demonstrated alterations in gene expression, loss of heterozygosity, and epigenetic changes in the stroma of human cancers (29,(34)(35)(36)(37)(38)(39)(40)(41). We did not observe any of these as DNA copy number changes; instead, we found changes in genes, some of whose connection to cancer was previously documented, and some where the connection was just plausible.…”
Section: Our Detection Of Any Changes At All (Especially the Deletions)contrasting
confidence: 38%
“…Various studies have demonstrated alterations in gene expression, loss of heterozygosity, and epigenetic changes in the stroma of human cancers (29,(34)(35)(36)(37)(38)(39)(40)(41). We did not observe any of these as DNA copy number changes; instead, we found changes in genes, some of whose connection to cancer was previously documented, and some where the connection was just plausible.…”
Section: Our Detection Of Any Changes At All (Especially the Deletions)contrasting
confidence: 38%
“…In fact, stromal changes coevolve with cancer development and result from a variety of epigenetic events (106)(107)(108)(109)(110). Chromosomal and/or genetic alterations, including loss of P53 (111)(112)(113)(114)(115)(116)(117), have also been reported to occur in the tumor stroma, although the significance of these findings has been questioned (107,110).…”
Section: Mesenchymal Stromal Alterationsmentioning
confidence: 93%
“…For example, cancer cells embedded in stroma are 10-to 100-fold more tumorigenic than cancer cells alone (12)(13)(14). Often, the majority of the cells in a solid tumor are stromal cells; these nonmalignant cells are generally genetically stable, although epigenetic and chromosomal abnormalities have been previously described (15)(16)(17)(18)(19). Because stromal cells cannot escape as mutant variant cells, targeting the stroma of solid tumors is an important focus for various types of therapies using chemicals (such as small-molecule tyrosine kinase inhibitors), radiation, or biologicals (e.g., antiangiogenic agents, growth factor traps, immunizations, or gene delivery that blocks endothelial signaling) (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%